Attention network to adolescents in situations of violence: perceptions of health professionals - Cláudia Fabiane Gomes Gonçalves; Lygia Maria Pereira da Silva; Ana Carolina Rodarti Pitangui (Universidade Federal de Goias, 2015)
The study aimed to comprehend perceptions of health professionals about the configuration of links between health services and institutions involved in the network to cope with violence against adolescents. An exploratory descriptive study of qualitative approach, conducted in 2013. Service managers of a reference hospital that attends violence cases participated in the study. The hospital was located in a capital at the northeast region of Brazil. Data were collected by filling the map of connections and semi-structured interviews, analyzed through content analysis technique, theme analysis. The subjects recognize health service in the attention network as relevant, however they identified political and structural limits. In conclusion, the attention network is valued, but considered insufficient and lacking specific technical norms. The strengthening of institutional links is necessary in a way that networks will effectively contribute to actions of integral, inter-sectoral and interdisciplinary character.